Hubungan Variasi Jumlah Lubang Chlorine Diffuser dengan Penurunan Total Coliform Air Limbah di RSUD Kota Yogyakarta (Poltekkes Kemenkes Yogyakarta, 2010)
The Yogyakarta City General Hospital already have a processing unit needed for the yielded liquid waste before it is disposed into water body. However, due to the damage caused by the May 2006 earthquake at the disinfection dripping tool, the disinfection activites were halted. On May 2008, the total coliform num- ber was found exceeding the maximum limit permitted by the regulation. So that, the purposed of this study is to understand the effect of hole number varia- tion in chlorine diffuser for declining the total coliform, by conducting an experi- ment with pre-test post-test only design. The data was analyzed with Pearson correlation test and was found that the total coliform decreased along with the higher number of the hole at 0,762 l/second debit. The total coliform obtained from hole variation of 20, 25 and 30 were fulfilled the requisite, meanwhile the 15 one was not. The subsequent function test showed that three day use of 25 hole chlorine diffuser still could reduce the total coliform of the liquid waste under the maximum treshold.